Biomedical Engineering Systems and Technologies - Fred, Ana (Springer, 2017)
This book constitutes the refereed proceedings of the International Joint Conference on Biomedical Engineering Systems and Technologies, BIOSTEC 2008, held in Funchal, Portugal, in January 2008. The 65 revised full papers and 189 revised short papers together with 86 poster presentations presented were carefully reviewed and selected from 494 submissions. The papers are organized in topical sections on biodevices, biosignals as well as healthinf.